Psychological dispositions that regulates decision-making process of drug addicts - Darvishov, Nariman (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2019)
The article is devoted to the research of dispositions that regulates decision-making process of substance addicts. Decision making process is often marked as one of a key links, that leads to addiction and then became impaired of its consequences – behavior altering and comorbid disorders of cognitive functioning. Defining this premorbid and comorbid specific could be helpful with understanding of addiction phenomena as whole. Comparing two groups by Mann-Whitney statistic criteria — a group of substance addicts and group of non-addicts have shown a list of specific tendencies in the manifestation of personal dispositions that confirmed as decision-making moderators. For the group of addicts is more inherently to have a higher degree of hypervigilance and intuitive ability, than for a control group, less inherently to have a higher level of vigilance, tolerance for ambiguity, as well as high intolerance for ambiguity. This points to tendency to make decisions in more impulsive way, and make more biased processes of rational regulation, especially in stress-rich environment. As for the perception of the temporal perspective, the orientation towards the hedonistic "here and now" before future consequences is more appropriate, combining with enhanced negative-past perception. Therefore, addicts time perception is another important axis of decision-making process analysis. In general, discovered features in individual dispositions of addicts, could point to the style-specific signature of decision-making process that can be localized within the predominance of implicit, rapid, intuitive processes, mostly impulsive in the degree of self-control and focused on the present, instead of taking long-term perspectives and conscience into the process. Such features must be taken into account in further rehabilitation program development.